Antecedents of Positive Word of Mouth and its Effects on Attitude toward Product - Morteza Soltani; Morteza Khavari (International Journal of Management, Accounting and Economics, 2015)
Regarding to interpersonal and informal nature of word of mouth, this advertising practice always is considered as a reliable communication source and a potential power playing a critical role in customers’ decision making process. According to the prominence of word of mouth in the customers’ decision making process, the present research tried to study some features of listener (background knowledge, purchase involvement) and some features of the speaker or the source (expertise, experience, evidences, and reliability) that cause listener to apply it encountering word of mouth by proposing a model. This is an applied study in term of goal and a descriptive-correlation study in term of methodology. Research statistical population included students of one of Tehran major government universities. Data collected using questionnaire and analyzed by structural equations model using Smart pls2 software. Research results showed that four features of listener are directly related to applying word of mouth by listener. Further, the two factors of purchase involvement and listener background knowledge only moderate the relationship among experience, reliability and the evidences presented by source by using word of mouth.